Rádios comunitárias: conflitos e negociações na configuração de redes de poder e identidades sociais - Polivanov, Beatriz Brandão (2008)
Based mainly on two case studies we carried out with the self-entitled community radios Novos Rumos and Onda Livre both settled in Baixada Fluminense , this work aims at reflecting on how the political and social interactions between people involved with community radios, representatives of the Federal Government (more specifically the Ministry of Communications) and other agents and agencies work, in order to understand how the construction of these agents‟ identities seems to be related to their discourse. We intend to examine the negotiations between the agents, their interests, requests, and some problematic questions, as a means to discuss about the control and power strategies used by the agents. In order to do so, we propose the utilization of the concept of network to understand that the social relations between the agents are fluid and constantly re-built, in accordance with the agents‟ interests. By trying to perceive the complexities in the relations between the agents, we hope to contribute for the study of community media.